Comparative Analysis of Intracellular and in vitro Antioxidant Activities of Essential Oil From White and Black Pepper (Piper nigrum L.) - Wang, Ying; Wang, Liang; Tan, Jin; Li, Rong; Jiang, Zi-Tao; Tang, Shu-Hua (Frontiers in Pharmacology, 2021)
Ethnopharmacological relevance: Pepper essential oils owned potential immunomodulatory, anti-tumor and anti-cancer activities, indicating pepper exhibited the potential to prevent or attenuate carcinogenesis as therapeutic tools. However, the related mechanism remains unelucidated. Aim of the study: The present study aims to provide reasonable information for the explanation of the dissimilarity of the essential oils from white (WPEO) and black pepper (BPEO). Materials and Methods: WPEO, BPEO and their single active component, as well as the synthetic antioxidants were compared by the cell model methods and chemical methods, including intracellular antioxidant activity (CAA), total antioxidant activities (TAA), superoxide radical (SR), hydroxyl radical (HR), DPPH radical (DR) scavenging activities and inhibition ability of lipoprotein lipid peroxidation (ILLP). Results: The median effective concentration (EC50) values (mg/mL) of WPEO and BPEO of SR, HR, DR and ILLP were 0.437 and 0.327, 0.486 and 0.204, 7.332 and 6.348, 0.688 and 0.624 mg/mL, respectively. The CAA units of WPEO and BPEO were 50.644 and 54.806, respectively. CAA, DR and TAA of BPEO were significantly higher than those of WPEO (p < 0.05). The BPEO and WPEO can be differentiated as the former has higher correlations with 3-carene, α-pinene, β-pinene and limonene while the latter has higher caryophyllene correlation. Besides, the WPEO and BPEO have a good intracellular scavenging ability of reactive oxygen species in HeLa cells. Conclusions: Generally, pepper oil has stronger activities than single components, indicating that pepper is a broad-spectrum natural antioxidant.